International stakeholder perspectives on One Health training and empowerment: a needs assessment for a One Health Workforce Academy - Sullivan, Ava; Ogunseitan, Oladele; Epstein, Jonathan; Kuruchittham, Vipat; Nangami, Mabel; Kabasa, David; Bazeyo, William; Naigaga, Irene; Kochkina, Olesya; Bikaako, Winnie; Ahmad, Nur; Yawe, Agnes; et al. (BioMed Central, 2023)
Background: One Health is defined as an integrated, unifying approach that aims to sustainably balance and optimize the health of people, animals and ecosystems; this approach attracts stakeholders from multiple sectors, academic disciplines, and professional practices. The diversity of expertise and interest groups is frequently and simultaneously framed as (1) a strength of the One Health approach in the process of understanding and solving complex problems associated with health challenges such as pathogen spillovers and pandemics and (2) a challenge regarding consensus on essential functions of One Health and the sets of knowledge, skills, and perspectives unique to a workforce adopting this approach. Progress in developing competency-based training in One Health has revealed coverage of various topics across fundamental, technical, functional, and integrative domains. Ensuring that employers value the unique characteristics of personnel trained in One Health will likely require demonstration of its usefulness, accreditation, and continuing professional development. These needs led to the conceptual framework of a One Health Workforce Academy (OHWA) for use as a platform to deliver competency-based training and assessment for an accreditable credential in One Health and opportunities for continuing professional development. Methods: To gather information about the desirability of an OHWA, we conducted a survey of One Health stakeholders. The IRB-approved research protocol used an online tool to collect individual responses to the survey questions. Potential respondents were recruited from partners of One Health University Networks in Africa and Southeast Asia and international respondents outside of these networks. Survey questions collected demographic information, measured existing or projected demand and the relative importance of One Health competencies, and determined the potential benefits and barriers of earning a credential. Respondents were not compensated for participation. Results: Respondents (N = 231) from 24 countries reported differences in their perspectives on the relative importance of competency domains of the One Health approach. More than 90 of the respondents would seek to acquire a competency-based certificate in One Health, and 60 of respondents expected that earning such a credential would be rewarded by employers. Among potential barriers, time and funding were the most cited. Conclusion: This study showed strong support from potential stakeholders for a OHWA that hosts competency-based training with opportunities for certification and continuing professional development.